Diplomasi Pertahanan Dan Militer Pemerintah Australia Dengan Pemerintah Myanmar Di Tengah Terjadinya Pelanggaran Hak Asasi Manusia Terhadap Etnis Rohingya Tahun 2018 - Amin Nino, Patricia Gracia; Dharmiasih, D.A Wiwik; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT   This research aims to explain how Australian defense diplomacy in the form of defense and military cooperation with the Government of Myanmar in the midst of human rights violations against the Rohingya Ethnic in 2018. Australia's defense and military cooperation aims to gain access to enter and communicate with the Government of Myanmar and provide advice in overcoming Rohingya Ethnic issues. The cooperation will take the form of humanitarian assistance, disaster relief and peace operations training or joint training. This research uses a descriptive qualitative method. The conceptual framework used is Defense Diplomacy. The conceptual framework used is Defense Diplomacy.. Keywords: Australia, Myanmar, Defense Diplomacy